Block the light and sleep well: Evening blue light filtration as a part of cognitive behavioral therapy for insomnia - Janků, Karolina; Šmotek, Michal; Fárková, Eva; Kopřivová, Jana (Chronobiology international, 2020)
The objective of the present study was to assess the effect of combining CBT-I with wearing blue-light blocking glasses 90 min prior to bedtime on subjective and objective sleep parameters and daily symptoms (anxiety, depression, hyperarousal). Thirty patients (mean age 48.1 ± 16.13 years, range 21-71, 15 men/15 women) completed a CBT-I group therapy program, with groups randomly assigned to either "active" (blue-light filtering glasses) condition or "placebo" (glasses without filtering properties) condition. Patients were continually monitored by wristwatch actigraphy, kept their sleep diaries and completed a standard questionnaire battery at admission and after the end of the program. Statistical analyses showed a greater reduction of BAI score in "active" (4.33 ± 4.58) versus "placebo" (-0.92 ± 3.68) groups of patients [F = 6.389, p = .019, Cohen's d = 1.26] and significant prolongation of subjective total sleep time in "active" (-36.88 ± 48.68 min.) versus "placebo" (7.04 ± 47.50 min.) [F = 8.56, p < .01, d = 0.91] group. When pre- and post-treatment results were compared in both groups separately, using paired-samples t-tests, significant differences were observed also in the active group for BDI-II score (t = 3.66, p = .003, Cohen's d = 0.95) and HAS score (t = 2.90, p = .012, Cohen's d = 0.75). No significant differences were found in the placebo group. In active group, there was also a significant reduction of subjective sleep latency (t = 2.65, p = .021, d = 0.73) and an increase of subjective total sleep time (t = -2.73, p = .018, d = -0.76) without change in objective sleep duration which was significantly shortened in the placebo group. We provide further evidence that blocking short-wavelength light in the evening hours may be beneficial for patients suffering from insomnia.
Keywords: cirkadiánní rytmus; Aged; Cognitive Behavioral Therapy; výsledek terapie; aktigrafie; Circadian Rhythm; lidé; lidé středního věku; senioři; ženské pohlaví; kognitivně behaviorální terapie; Female; mužské pohlaví; Sleep Initiation and Maintenance Disorders; Young Adult; Adult; spánek; poruchy iniciace a udržování spánku; Middle Aged; Treatment Outcome; Humans; Actigraphy; dospělí; Male; mladý dospělý; Sleep